Estimation of patent foramen ovale size using transcranial Doppler ultrasound in patients with ischemic stroke. Issue 1 (30th September 2021) - Grisold, Anna; Rinner, Walter; Paul, Anna; Gabriel, Harald; Klickovic, Uros; Wolzt, Michael; Krenn, Martin; Zimprich, Fritz; Bsteh, Gabriel; Sycha, Thomas
Abstract: Background and Purpose: Patent foramen ovale (PFO)is associated with cryptogenic stroke, especially in young adults. Transcranial Doppler (TCD) ultrasound is used as a screening tool before transesophageal echocardiography (TEE). However, the use of Valsalva maneuver (VM) to identify a right‐to‐left‐shunt underlies interindividual variability. Here, we aimed to assess whether a pressure‐controlled standardization of VM is useful to estimate PFO size. Methods: We included patients aged 18–80 years with a PFO according to TEE. Subjects underwent TCD with microembolic signals (MES) counted under four pressure conditions (i.e., at rest, 15 mbar, 40 mbar, and maximum expiratory pressure). Findings were correlated with TEE‐based PFO size. The predictive value of TCD at rest and VM‐based TCD for PFO size estimation was assessed by stepwise multivariate linear regression models and multiple cross‐tab‐analyses. Results: We screened 203 subjects after a cerebrovascular event, of which 78 (48 males [61.5%], median age 55 years [22–80]) with PFO were included. We found an association between MES count and expiratory pressure ( p < .001). Predefined MES count categories at TCD pressure conditions correlated significantly with PFO size measured by TEE. We propose a PFO size estimation model based on TCD at rest and under VM, which classified PFO size correctly in 64.1% with the highest accuracy for small PFOs. Conclusion: Our data provide evidence that TCD with step‐wise barometric standardization allows an estimation of PFO size with good accuracy. Though TCD will not replace TEE in future, this might be of clinical value in circumstances where TEE cannot be easily performed.